The effect of acid buf and combinations of acid buf and socium bicarbonate in dairy cow diets on production response and rumen parameters - Calitz, Tanja (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2009.